A data mining approach to documenting global floating building projects: Design trends, material and structural systems - Mark Cyril Francis; Mohd Khairul Azhar Mat Sulaiman; Nurakmal Abdullah @ Goh; Ruzanah Abu Bakar; Nur Fadilah Darmansah; Siti Syariazulfa Kamarudin; Elis Mardzianah Datuk Hj, Mazlan; Azilah Baddiri (International Journal of Research and Scientific Innovation, 2025)
Floating architecture has emerged as a viable response to urbanization, climate change, and increasing sea levels. The absence of a centralized database cataloguing constructed floating buildings globally impedes thorough research and practical implementation. This paper aims to systematically gather, analyses, and categories data on floating building globally using the method of web mining and data mining techniques to collect data. The Arch daily website was the primary source for web mining, employing 'floating architecture' as the main term for the extraction process in 143 countries globally, focusing on the construction of floating buildings from 2000 to 2025. The item studied include and classify into Continent, Nation, year of project completion, building Category, average floor area, structure and materials. Key statistics reveal that Europe leads in floating construction, accounting for 53.1% (34 structures) of the worldwide total. The Netherlands is the most engaged nation, donating 15% (9 buildings), followed by the United States (10%, 6 buildings) and Germany, Thailand, and Ecuador (6.7% each, 4 buildings). Completion records reveal a peak in 2021, with eight structures erected. Small residences constitute 53.3% (16 units), whereas places of assembly account for 36.7% (11 units). All constructions use pontoons as their foundational supports. Plastic (48%) and concrete (33%) are the primary materials, together comprising 81% of occurrences. This study establishes a foundational dataset for future research, providing essential information regarding the development, regional patterns, and technological inclinations of floating architecture. The findings underscore the potential of pontoon-supported structures and highlight material enhancements as a vital area for future development in this emerging field.